“I’m a Human Being, I Deserve Better:” Understanding Black Women’s Experiences with Selective Dignity Violations as Tenured Faculty at Predominantly White Academic Workplaces - Josie Andrews (Adult Education Research Conference, 2024)
A larger narrative inquiry study regarding professional identity development revealed that Black women experienced selective dignity violations as tenured faculty at predominantly White academic workplaces.
Keywords: selective dignity violations; tenured Black female faculty; professional identity development